Arbuscular mycorrhizal fungi - An underground resource for sustainable upland agriculture - Yimyam N. (2014)
Rotational shifting cultivation is well known for its sustainability, especially with the luxury of long cycles. Less well recognized are contributions from underground. This paper shows how arbuscular mycorrhizal (AM) fungi contribute to productivity and sustainability of a shifting cultivation system with rotational cycle much shortened by pressure on the land. Farmers of the village of Huai Tee Cha in northern Thailand make a living from shifting cultivation on acidic infertile soil with rotation cycle reduced from 20 years to only 7 years. Farmers attribute satisfactory yield of their upland rice and associated swidden crops to Pada (Macaranga denticulata), a fallow enriching tree that occurs naturally in the field. Vegetation sampling in farmers' fields found that Pada accumulates exceptional amounts of biomass and nutrients. The roots of Pada and food crops in the field were heavily infected with AM fungi, with 29 species of the fungi in 6 genera identified. In controlled experiments on steam sterilized acidic soil deficient in phosphorus (P), Pada was found to be almost completely dependent on AM fungi. Infection with the fungi increased growth and nutrient uptake to the same extent as fertilizer P application. Major food crops in the system have also been found to be heavily infected by the AM fungi. The role of AM fungi in sustainability of this upland cropping system via nutrient accumulation and recycling by Pada is clear. However, the direct impact on growth and productivity of all the crops, semi-domesticated and wild species, through root colonization and networks of extended hyphae, remain to be explored.